2009
DOI: 10.1186/cc8145
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of propofol-related infusion syndrome in critically ill adults: a prospective, multicenter study

Abstract: IntroductionWhile propofol is associated with an infusion syndrome (PRIS) that may cause death, the incidence of PRIS is unknown. Determining the incidence of PRIS and the frequency of PRIS-related clinical manifestations are key steps prior to the completion of any controlled studies investigating PRIS. This prospective, multicenter study sought to determine the incidence of PRIS and PRIS-related clinical manifestations in a large cohort of critically ill adults prescribed propofol.MethodsCritically ill adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 67 publications
0
110
0
13
Order By: Relevance
“…PRIS is a rare complication, which is associated with high doses (>4 mg/kg/h) and long-term use (>48 h) of propofol, concomitant steroid therapy, high consumption of vasopressors, and patient age <18 years [38,39]. The incidence of PRIS is~1 % in adult patients [40]. There are no valid data for children, but propofol use in children in pediatric intensive care units (PICUs) appeared to be safe when doses did not exceed 4 mg/kg/h and use was restricted to <24 h [41,42].…”
Section: Pathophysiologymentioning
confidence: 99%
“…PRIS is a rare complication, which is associated with high doses (>4 mg/kg/h) and long-term use (>48 h) of propofol, concomitant steroid therapy, high consumption of vasopressors, and patient age <18 years [38,39]. The incidence of PRIS is~1 % in adult patients [40]. There are no valid data for children, but propofol use in children in pediatric intensive care units (PICUs) appeared to be safe when doses did not exceed 4 mg/kg/h and use was restricted to <24 h [41,42].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In generale gli agonisti Alfa-2 sembrano inibire la conduttanza ionica attraverso i canali del calcio di tipo L-o P-e facilitare la conduttanza attraverso i canali del potassio calcio-attivati e voltaggio-regolati. Gli effetti degli Alfa-2 agonisti sono facilmente reversibili ad opera degli antagonisti Alfa-2 adrenergici, proprietĆ  che costituisce un indubsi accumulano ad alte dosi [30]. Sulla base delle linee guida disponibili nĆ© midazolam nĆ© propofol sono raccomandati per la sedazione a lungo termine.…”
Section: Alternative Terapeutiche Disponibili E Unmet Needunclassified
“…It is complicated to determine the incidence of propofol-related infusion syndrome (PRIS) because many of the PRIS-associated clinical manifestations may reflect either pharmacologic manifestations of propofol (eg, bradycardia) or manifestations of critical illness (eg, metabolic acidosis). In the first large prospective study involving more than 1000 patients, 3 PRIS was defined as development of metabolic acidosis and cardiac dysfunction after the initiation of propofol along with at least one of the following: rhabdomyolysis, hypertriglyceridemia, or renal failure. Although the study had many limitations, the reported incidence of PRIS was 1.1%.…”
Section: Introductionmentioning
confidence: 99%